Tachydromia incompleta - Shamshev, Igor V.; Grootaert, Patrick (Zenodo, 2024)
Tachydromia incompleta (Becker) (Fig. 9) Tachista incompleta Becker, 1900: 33 (♀), Pl. 2, fig. 1. Type locality: Russia, “Insel Nikander” [= Nikandrovskie Islands, mouth of Yenisei River, Krasnoyarskiy Territory]. Tachydromia anderssoni Chvála, 1970: 494, figs 73–75. Type locality: Sweden, Karesundo [= Karesuando, Torne lappmark]. Tachydromia incompleta : Chvála, 1975: 242, figs 574–576, 762 (synonymy of T . anderssoni ). Notes on type series. The holotype of T. incompleta is deposited in Helsinki (MZH) and was examined by I.S. in 2019. In addition, the holotype and two paratypes of T . anderssoni were examined in Lund (MZLU) and Moscow (ZMMU), respectively. Material examined. NORTH AMERICA. CANADA. Alberta: Dunvegan, N side Peace River, 11– 25.vii.1995, S. Boucher (1 ♀, CNC); same locality, pan trap in grass, 19–28.vi.1995, S. Boucher (1 ♀, CNC). EURASIA. RUSSIA. Altay Republic: middle flow of river Ulandryk, 27.vi.1964, Grunin (1 ♂, ZISP); Kosh-Agach distr., 60 km SSW Kosh-Agach, 2200m, 49°38´N, 88°29´E, 29.vi.2014, leg. I. Shamshev (8 ♂, 9 ♀, ZISP). Sakha (Yakutia) Republic: Verkhoyansk, shore of river Yana, willow shrub, 12–14.viii.1972, Gorodkov (1 ♂, 3 ♀, ZISP); Udachny, 21.vii.1988, Gorodkov (1 ♀, ZISP); Ebelyakh, shore of river Anabar, Gorodkov (1 ♀, ZISP); left shore of river Yana, near Verkhoyansk, sedge swamp, 23.vii.1974, Nartshuk (1 ♂, ZISP); Indigirka River, mouth of River Inyali, 20.vi.1976, V. Kovalev (1 ♀, ZMMU). SWEDEN: Abisko, Lpl., 3.viii.1951, J. R. Vockeroth (1 ♀, CNC); same locality, 13.viii.1951, J. R. Vockeroth (1 ♂, CNC). Recognition. The species is distinguished by the following combination of characters: palpus without black subapical seta; proepisternum shiny. Male: palpus yellow on basal part, blackish brown on apical 1/4 to 1/2; mid tibia with 2 closely set, long subapical setae posteriorly. Female: palpus uniformly pale yellow. Redescription. The species was fully redescribed and illustrated by Chvála (1970 [as T . anderssoni ], 1975). Only crucial characters are provided herein. ...